2017
DOI: 10.15766/mep_2374-8265.10662
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Approach to Teaching Obesity Management to Medical Students

Abstract: Introduction: The need for education of future and current providers in evidence-based management of obesity and the release of new treatment guidelines prompted the development of a resource for use in the education of medical students and residents. Methods: A self-contained module was developed to provide an overview of recent guidelines for obesity management utilizing evidence-based medicine while debunking popular myths associated with available weight-loss strategies. The module was delivered over 15 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Our CBL module helps close the gap in this area of medical education by providing a resource that both explores the interplay between obesity and reproductive health and delivers this information in an effective and engaging way. Although some educational and teaching resources exist regarding medical management of obesity alone, 4 our module builds upon them by implementing the fundamentals of obesity management in the setting of reproductive health care and pregnancy and including reflection about implicit bias and how it affects health care delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our CBL module helps close the gap in this area of medical education by providing a resource that both explores the interplay between obesity and reproductive health and delivers this information in an effective and engaging way. Although some educational and teaching resources exist regarding medical management of obesity alone, 4 our module builds upon them by implementing the fundamentals of obesity management in the setting of reproductive health care and pregnancy and including reflection about implicit bias and how it affects health care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…We further extended our search to other databases, including PubMed, Association of Professor of Gynecology and Obstetrics, and the Endocrine Society, and found that while plenty of publications regarding the interplay of obesity and reproductive health existed, none were formatted to serve as a teaching tool. Some educational and teaching resources consider medical management of obesity from the perspective of an internist, 4 but there remains a lack of readily available learning resources for medical students on the management of obesity as it relates to reproductive health and, specifically, the effects of bariatric surgery on pregnancy. As a result, our module was designed to build upon these resources by presenting the knowledge to guide this type of management from the viewpoint of an obstetrics provider.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications in MedEdPORTAL address topics in nutrition education, including the use of interprofessional education in diet assessment and counseling, obesity management, and online learning modules for obesity management and exercise. [6][7][8][9] Our interactive didactic session adds to this group of resources by addressing select popular diets and diet patterns and providing practical tools that clinicians can use in dietary assessment and counseling. This combination of teaching both key evidencebased nutrition information and basic nutrition tools makes the session high yield and directly applicable to clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…Several MedEdPORTAL publications deal with obesity counseling and behavioral change curricula, and one offers a wellness program for undergraduate medical students, but none specifically focus on the discipline of lifestyle medicine that simultaneously emphasizes patient and personal wellness. [13][14][15][16][17] Recognizing these curricular gaps at our own institution and appreciating the unique stressors and obstacles our students face in trying to make positive lifestyle choices, we developed and delivered a series of interactive workshops with the goal of teaching students about the lifestyle and behavioral factors that affect the health of both the patients they care for and themselves. We used the combined instructional modalities of didactic presentations, small-group discussions, and individual reflective practices to deliver curricular content and engage students.…”
Section: Introductionmentioning
confidence: 99%